In vitro Inhibitory Effect of Probiotics on Helicobacter pylori (African Journal of Biomedical Research, 2023)
The use of probiotics for the inhibition of Helicobacter pylori, could present a low-cost, large-scale alternative solution to prevent or decrease Helicobacter pylori colonization. This study is however designed to evaluate the antibacterial activity of probiotics (Lactobacillus) produced by Lactic acid bacteria against Helicobacter pylori. The study also focuses on the isolation and characterization of Helicobacter pylori and different lactic acid bacteria from stool sample of ulcer patients and local rice water respectively. The effect of probiotics on Helicobacter pylori growth and Helicobacter proliferation were examined in vitro of the isolates identified from this study, the probiotic Lactobacillus acidophilus strain NK-S10 had the highest zone of inhibition of 18mm against Helicobacter isolate Hp3 while Lactobacillus spp had the least inhibition zone of 2mm against Helicobacter pylori isolate Hp1. Therefore, this study demonstrates the lethal effect probiotics could have on Helicobacter pylori growth and proliferation. Thus, the administration of probiotics can decrease the frequency of diarrhea, a frequent side effect of traditional anti- Helicobacter pylori tri-therapy.